RESPON PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) VARIETAS RUBARU TERHADAP BIOCHAR SEKAM PADI DAN MIKORIZA DI VERTISOL - Slamet Supriyadi; Fahmi Arief Rahman; Beti Dwi Purwati (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2022)
Cultivating red onion on a Vertisol during rainny season could face to physical and chemical problems from the soil. Application of biochar and mycorrhiza can improve soil quality both physical and chemical properties of Vertisol. The objective of this study was to investigate the effect of rice husk biochar and arbuscular mycorrhizal fungus (AMF) on growth and yield of red onion grown on a vertisol. The research was carried out at the Agrotechnology Research Station, University of Trunojoyo Madura from December 2018 to February 2019. The experiments were arranged on Split Plot Design (SPD) with the main plots were the biochar treatments and the sub plots were AMF applications. Two rates of biochar applications namely B0 (no biochar) and B1 (10 ton/ha), and four rates of AMF applications involving M0 (no mycorrhiza), M1 (2.5 g/plant), M2 (5 g/plant) and M3 (10 g/plant), were employed. No P fertilizer was applied on three AMF treatments (M1, M2, and M3). There were 8 combination treatments, and each treatment was replicated four times to end up in 32 experimental units. The results showed that there was no interaction between biochar and AMF treatments on all observed parameters. Biochar increased the number of leaves at 4 and 6 WAP (week after planting), the number of roots, and the weight of fresh tubers, and dry tubers that were suitable for storage. Mycorrhizal (AMF) application significantly influenced the number of leaves at 2 and 6 WAP, number of roots, wet weight of tubers, dry weight of tubers, and percentage of AMF root colonization. The application of rice husk biochar and AMF increased tuber yields respectively up to 17.21% and 19.58% compared to that of control.